Philosophy at the Crossroads - Ballard, Edward G. (Book collections on Project MUSE., 1971)
A study of the course and consequences of modern Western thought, this volume deals with some of the most crucial philosophical questions of our time. In Philosophy at the Crossroads, Edward G. Ballard defines philosophy as the interpretation of archaic experience -- that transition or change which forces one to attempt to understand, and usually reformulate, the basic notional framework within which order and value are discovered. He illustrates the relevance of this definition in the work of six philosophers -- Plato, Descartes, Hume, Kant, Jusserl, and Heidegger -- and develops an interpretation of several important lines of growth in Western philosophy. The first transition Professor Ballard examines is the movement from pre-Homeric, oral, and poetic culture to the Socratic, written, intellectualist culture. The new tradition is evident in Plato, who is at once mythmaker and humanist and also the father of the sciences. Plato, says Ballard, instituted an uneasy balance between a sciencelike interest in the world and a humanist self-care by defining the former as a means to the humanistic end. He demonstrates that this uneasy balance is an important clue to understanding Western intellectual history. The author traces the growth and various directions of Western thought through Heidegger, discusses its contemporary status, and speculates on the potential for its future development.